THE EFFECT OF ACCOUNTING INFORMATION SYSTEM QUALITY, FINANCIAL LITERACY, AND PERCEIVED EASE OF USE ON THE REPEATED USE OF THE WONDR BY BNI APPLICATION - Anak Agung Trisnadewi Adnyani; Made Yenni Latrini (Adisam Publisher, 2025)
The advancement of financial technology has driven the banking sector to continuously innovate in providing digital services, one of which is the Wondr by BNI mobile banking application. This study aims to examine the effect of accounting information system quality, financial literacy, and perceived ease of use on the repeated use of the Wondr by BNI application. A quantitative approach was employed, utilizing a survey method through questionnaires distributed to 151 undergraduate students of the 2021 cohort in the Accounting Study Program at Udayana University. The data analysis technique used was multiple linear regression assisted by SPSS. The results reveal that accounting information system quality, financial literacy, and perceived ease of use have a positive and significant effect on the repeated use of the Wondr by BNI application. These findings provide valuable insights and support both the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) in explaining the financial technology usage behavior among the younger generation, particularly university students.